2001
DOI: 10.1088/0953-8984/13/50/316
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure Raman spectroscopic study of zirconium tungstate

Abstract: Raman spectroscopic measurements on negative-thermal-expansion (NTE) material zirconium tungstate Zr(WO4)2 at 20 K over the complete range of phonon frequencies yield 39 out of the predicted 54 optical phonons. The modes are assigned as lattice modes, and translational, librational and internal modes of the WO4 ion. High-pressure measurements in a diamond anvil cell (DAC) have revealed that in addition to the low-frequency rigid-unit modes (RUMs) several other phonons, including the bending modes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 59 publications
10
94
1
Order By: Relevance
“…On the other hand, at ambient temperature, the system is likely to get trapped in a metastable amorphous (disordered) state while attempting to decompose under the application of pressure. The reported PIA in zirconium tungstate at 2.1 GPa and ambient temperature 16 and pressureinduced decomposition (PID) into mixture of simple oxides at 0.6 GPa and 1073 K 17 are consistent with this model. The condition ⌬V Ͻ 0, where ⌬V is the volume change upon decomposition, has been identified as a criterion for PIA at ambient temperature.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, at ambient temperature, the system is likely to get trapped in a metastable amorphous (disordered) state while attempting to decompose under the application of pressure. The reported PIA in zirconium tungstate at 2.1 GPa and ambient temperature 16 and pressureinduced decomposition (PID) into mixture of simple oxides at 0.6 GPa and 1073 K 17 are consistent with this model. The condition ⌬V Ͻ 0, where ⌬V is the volume change upon decomposition, has been identified as a criterion for PIA at ambient temperature.…”
Section: Introductionsupporting
confidence: 72%
“…It consists of corner-linked ScO 6 octahedra and MoO 4 tetrahedra. 18 Several other network structures such as zirconium tungstate, 16 scandium tungstate, 19 and Sm, Eu, and Gd molybdates 20 are found to undergo PIA at rather moderate pressures of 2 -5 GPa. Among these scandium molybdate is a unique system which exhibits amorphization in two stages.…”
Section: Introductionmentioning
confidence: 99%
“…The slight shrinkage of the unit cell volume could be related to partial decomposition and the release of nitrogen. Pressure-induced phase decomposition has been reported in many oxides with various crystal structures [25,26]. The FeTiO 3 perovskite-type oxide (as a high pressure polymorph) was also decomposed into a mixture of rock-salt type "FeO" and TiO 2 at high pressure above 67 GPa [27,28].…”
Section: Dielectric Property Of the High Pressure Compactsmentioning
confidence: 97%
“…The structure of Zr(WO 4 ) 2 and several other NTE materials consist of corner sharing tetrahedral and octahedral units. From Raman spectroscopic investigations on Zr(WO 4 ) 2 as a function of pressure and temperature, the phonons responsible for NTE have been identified, and it has been shown that in addition to the librational (rigid-unit) mode at 5 meV, several other phonons of much higher energy also contribute significantly to the NTE in this material [6][7][8][9]. Based on structural analysis transverse displacements of the shared oxygen atoms and consequent rotation of polyhedra [1] was suggested as the cause of NTE in Zr(WO 4 ) 2 .…”
mentioning
confidence: 99%